A new methodology to determine sorption curves from Flory Huggins parameters measured at solvent and polymer infinite dilution. (September 2016) - Camacho, Javier; Díez, Eduardo; Ovejero, Gabriel
Graphical abstract: Highlights: A new procedure to obtain Flory Huggins – composition curve from only two values of the Flory Huggins parameter. The methodology, validated with ten polymer-solvent systems, shows great agreement between literature and calculated values. The methodology has been employed to study the ethylene-vinyl acetate copolymer–solvent systems. Abstract: In this work, a new methodology to determine the solvent sorption curve (pressure-composition curves for the vapour-liquid equilibrium) of a polymer/solvent mixture, from the Flory Huggins data measured at the composition extremes of the binary mixture (infinite dilution of polymer, and infinite dilution of solvent) has been proposed. This methodology is based on the works of Bernard Wolf about the dependence of the Flory Huggins parameter, χ, on the polymer composition. The methodology was validated for ten different polymer/solvent systems, with an overall value of the Average Absolute Deviation (%AAD) between the literature and estimated pressure values around 1%. Once validated, the procedure was employed to obtain the sorption curves of several systems of interest for our research group: the binary mixtures of ethylene/vinyl acetate copolymer (EVA), the ones of its correspondent homopolymers, polyethylene (PE) and polyvinyl acetate (PVA), with cyclohexane, and the binary system polyvinyl acetate/methanol. For these systems, the Flory Huggins parameter values at infinite dilution of solvent and polymer were taken from our previous works (studies of inverse gas chromatography and intrinsic viscosity, respectively). Finally, from the previously obtained values, the dependence of the Wolf parameters on the vinyl acetate percentage was analyzed taking into account the excess properties.